2018
DOI: 10.2460/javma.252.4.457
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of limb fracture repair in rabbits: 139 cases (2007–2015)

Abstract: OBJECTIVE To evaluate outcome of limb fracture repair in rabbits. DESIGN Retrospective case series. ANIMALS 139 client-owned rabbits with limb fractures treated between 2007 and 2015. PROCEDURES Medical records were reviewed for information on fracture location, fracture treatment, and time to fracture healing. RESULTS 25 rabbits had fractures involving the distal aspects of the limbs (ie, metacarpal or metatarsal bones, phalanges, and calcaneus or talus). Fractures were treated in 23 of these 25 rabbits (exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 18 publications
3
25
0
2
Order By: Relevance
“…A group of GCRs presenting with femoral fractures were identified in our study which highlights the differences between our population and the population reported by Sasai et al . (, ), and which may have biased the otherwise generally even distribution of fractures between the appendicular long bones (femur, radius and ulna, and tibia) in our population. This suggests that GCRs may be predisposed to femoral fractures, but could also reflect that they are more likely to be referred with this type of fracture, given that they represent only a small proportion of all rabbits presenting to the hospital over the same time period.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…A group of GCRs presenting with femoral fractures were identified in our study which highlights the differences between our population and the population reported by Sasai et al . (, ), and which may have biased the otherwise generally even distribution of fractures between the appendicular long bones (femur, radius and ulna, and tibia) in our population. This suggests that GCRs may be predisposed to femoral fractures, but could also reflect that they are more likely to be referred with this type of fracture, given that they represent only a small proportion of all rabbits presenting to the hospital over the same time period.…”
Section: Discussionmentioning
confidence: 94%
“…In contrast, the tibia was reported to be the long bone most commonly fractured in a large cohort of smaller breed rabbits (Sasai et al . , ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations